THE RELATIONSHIP OF ALLOWANCE AND ANNUAL BONUS TO EMPLOYEE PERFORMANCE IN EXPORT IMPORT COMPANIES - Zakaria Harahap,; Rona Anggrainie,; Meirani Betriana,; Arman Syah Putra,; Bambang Harianto, (Journal of Innovation Research and Knowledge, 2022)
The background of this research is how to find out the relationship between annual bonus allowances and employee performance variables in a company engaged in the export-import sector. Therefore, with these three variables, it will be known that employee performance will affect what variables can improve performance employee. The method used in this study is to use quantitative methods by conducting a survey of 100 employees at a company engaged in the export and import sector. With this research, it can be seen what things can improve employee performance at the company. The problem raised in this study is how to find out the variables that affect the performance of employees at an import-export company. With these variables, it can be said that the performance of employees at the company. The purpose of this study is to find out what variables affect another variable. The variables raised in this study are the allowance variable from the variables represented by hypothesis 1 and hypothesis 2, hypothesis 1 produces a value of 0.003 which means that it is very influential and hypothesis 2 has a value 0.002 which has a heart greatly affects his heart, these two values can affect the dependent variable, namely the employee performance variable.